Determinants of Bid-Ask Spread in Indonesia: More Evidence from LQ45 - Herma Wiharno; Dede Sri Rahayu (Universitas Kuningan, 2018)
The investors are one of the important components of the capital market. The investors are the person who invests money in the company. In the capital market, the investors are helped by a broker. The broker helps the investors in overcoming the mismatch between price and quantity that is not in line with expectations. When an investor wants to buy a stock, the broker will ask the asking price and if an investor wants to sell investor’s shares, the broker will provide the bid price. The difference between the bid price and the asking price is called bid-ask spread. Bid-ask spread is the compensation given to the market maker for the services provided. There are several factors that affect the bid-ask spreads that are trading volume, variance return, market value, and return on equity. This study aimed to provide empirical evidence of the effect of trading volume activity, variance return, market value, and return equity on companies listed in the LQ45 index period of 2013-2016. The sample in this research used purposive sampling. The analysis method for this research was multiple regression models. The results of this research showed that trading volume activity, variance return, market value, and return on equity simultaneously influence bid-ask spread. Partially, trading volume activity has negative insignificantly effect on bid-ask spread. The independence of the board of commissioners has negative insignificantly effect on bid-ask spread. Variance return, market value, return on equity, and have a positive significant effect on bid-ask spread.Keywords: trading volume activity, variance return, market value, return on equity, bid-ask spread